The role of systemic inflammation in the pathogenesis of hyperkinetic disorder - Rauf F. Gasanov; Igor V. Makarov; Daria A. Emelina; Ilya V. Kravchenko; Ekaterina S. Prokhorenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
Hyperkinetic disorder (HD) is a common mental disorder in children and affects 5% of the population. In recent years, the important role of systemic inflammation in the pathogenesis of HD has been discussed. It is believed that the level of neutrophils, lymphocytes, platelets and monocytes, as well as their ratios, can serve as markers of systemic inflammation in HD. However, the question of the specificity of the data obtained remains open due to insufficient data. The specificity of markers of neuroinflammation and systemic inflammation, levels of hyperkinetic disorder remains insufficiently studied, which requires clarification in future studies with the exclusion of background residual organic pathology of the brain, inflammatory and autoimmune diseases in comparison not only with a group of healthy controls, but also with a group of patients with other mental disorders.